Spatially Heterogeneous Tubular Scaffolds for In Situ Heart Valve Tissue Engineering Using Melt Electrowriting. (15th February 2022) - Saidy, Navid Toosi; Fernández‐Colino, Alicia; Heidari, Behzad Shiroud; Kent, Ross; Vernon, Michael; Bas, Onur; Mulderrig, Shane; Lubig, Andreas; Rodríguez‐Cabello, José Carlos; Doyle, Barry; Hutmacher, Dietmar W.; De‐Juan‐Pardo, Elena M.; et al.
Abstract: Heart valve tissue engineering (HVTE) aims to provide living autologous heart valve implants endowed with regenerative capabilities and life‐long durability. However, fabrication of biomimetic scaffolds capable of providing the required functionality in terms of mechanical performance and tunable porosity to enable cellular infiltration remains a major challenge. Here, the additive manufacturing of bioinspired, spatially heterogeneous, tubular scaffolds enclosing the leaflets, inter‐leaflet triangles, and their interface for in situ HVTE using melt electrowriting (MEW) is demonstrated. The innovative platform enables the digital fabrication of scaffolds with ad hoc architecture (e.g., tunable location, specific fiber pattern, and orientation) and customizable geometry via a custom‐made control software. The user‐friendly interface allows for the definition of areas of the scaffold with specific patterns to obtain properties such as tunable J‐shaped stress–stain curve and anisotropy typical of the heart valve leaflet, compliant inter‐leaflet triangles, and reinforced curvilinear boundary between them. Heterogeneous, tubular, heart valve MEW scaffolds are then embedded with a microporous elastin‐like recombinamer (ELR) hydrogel to develop a soft‐network composite favoring cell infiltration and ensuring hemocompatibility. The acute systolic hemodynamic functionality of the MEW/ELR composite satisfies the ISO 5840 requirements, under aortic and pulmonary conditions. Abstract : The convergence of melt electrowriting, as advanced additive manufacturing technology, and elastin‐like recombinamers, as advanced bioactive materials, results in a versatile platform for the digital fabrication of bio‐inspired, spatially heterogeneous scaffolds for in situ heart valve tissue engineering, with low thrombogenicity and tuned porosity for cellular infiltration. This platform can be extended to other soft tissue engineering applications.